ECG changes in psychiatric patients on psychotropic medications. (4th February 2022) - Wong, S; Soliman, M; Cunningham, A; Ho, H; Johar, S
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Suicide and euthanasia accounts for 14.3% of deaths in those with psychiatric conditions. The rest are attributed to preventable causes such as cardiovascular disease, respiratory disease, and infections. Several psychotropic medications have been associated with sudden death due to their effect on prolonging QT interval, resulting in the development of a polymorphic ventricular arrhythmia, Torsades de Pointes (TdP). TdP may be self-limiting or lead to sudden cardiac arrest and death. Purpose: This study aims to evaluate the cardiotoxic effects of psychotropic medications. Method: This is a descriptive retrospective study of patients submitted to the local psychiatric wards within one year. Patients with psychotropic drug prescriptions were included while patients below 18 years old, pregnant, or did not have ECG performed were excluded. The control group consisted of sex- and age- matched patients with ECG conducted for occupational health purposes. Multiple regression models were conducted to investigate the predictors of significant ECG differences. Result: Of the 154 psychiatric inpatients admitted, exclusions were 44 patients due to exclusion criteria and 19 patients due to difficulty in physical file access. The study population (n = 91) had a mean age of 36.7 years old with 40.7% female and 59.3% male. The predominant diagnoses were schizophrenia and delusional disorders (58.2%). 86 psychiatric patients (94.5%) were prescribed antipsychotic drugs (APD). A significantly higher proportion of psychiatric patients has a history of smoking (p < 0.001), alcohol consumption (p = 0.001), and illicit drug use (p < 0.001). They also exhibited significantly more co-morbid illnesses including hypertension (p = 0.022), hyperlipidaemia (p = 0.013), diabetes (p = 0.026) and thyroid disease (p = 0.023) than the control population. Psychiatric patients had a significantly higher mean heart rate (79.9 vs 69.6 ms; p < 0.001) and QTc interval (452.2 vs 418.6ms; p < 0.001). Mean QTc interval was significantly longer for psychiatric patients in both male (454.2 vs 414.5ms; p < 0.001) and female (449.3 vs 425.6 ms; p = 0.029) gender. Psychotropic drug use is a significant predictor for both prolonged heart rate (p < 0.001) and prolonged QTc interval (p < 0.001). Electrolyte imbalance is a significant predictor of prolonged QTc interval only (p = 0.036). One year follow of both groups detected only 1 psychiatric patient with palpitation. Conclusion: Psychiatric patients on psychotropic medications have a longer baseline heart rate and QTc interval, which was not associated with MACE at 1 year. None of the underlying comorbidities and lifestyle choices were significant predictors of this. Electrolyte abnormalities and psychotropic drug use significantly predicted QTc prolongation. However, these findings were largely driven by APD use. A follow-up study of a longer period is recommended to investigate whether patients with prolonged QTc interval are of higher risk of MACE occurrence.